The Use of Activated Charcoal for Acute Poisonings - Juliana Bonilla-Velez; Juliana Bonilla-Velez; Darly J Marin-Cuero; Darly J Marin-Cuero (International Journal of Medical Students, 2017)
Poisoning results from the ingestion of or contact with harmful substances including overdose or incorrect use of any drug or medication. Decontamination measures prevent the absorption of the substance from the gastrointestinal tract to minimize systemic effects. Activated charcoal is the intervention most frequently used in the initial management of patients with acute intoxications. The use of activated charcoal has decreased over time, but there may be a subgroup of patients who would benefit from its use. In this review we describe the epidemiology of intoxications, the composition and pharmacology of activated charcoal, indications and dosing for use of single dose and multiple doses of charcoal, contraindications, complications and a summary for recommended use of this measure based on published studies.